Zoom Meeting and Dromology: Manifestations of the Folded World in the Lecture Process of University of Sumatera Utara Students - Malik, Rahman; Habibi , Abdillah; Jasmine, Humaira; Kinanti Putri, Karimah; Ruslina Hondro, Shelly (TALENTA Publisher, 2025)
ABSTRACT Zoom meetings are a tool used by University of North Sumatra students to hold lectures when a pandemic occurs or certain obstacles arise. The use of zoom meetings is based on efficiency and the many features available in it. Zoom meetings show a form of dromology and a manifestation of a folded world. Seeing how zoom meetings show the existence of a form of dromology and the manifestation of a folded world is the aim of this research. This research uses descriptive qualitative research methods. University of North Sumatra students were the subjects of this research. Observations and interviews are the primary data sources for this research. Meanwhile, secondary data regarding dromology and the use of zoom meetings was obtained from journals and websites on the internet. This research uses Miles and Huberman data analysis techniques. This research shows that dromology is visible in learning through Zoom Meetings which causes the lecture process to run in real time without any obstacles of distance, time and space which causes interactions between students and lecturers to become a blend of physical and virtual reality. reality. Meanwhile, the manifestation of a folded world can be seen from the existence of folded lecture rooms due to the use of Zoom, which causes the distance and time for lectures to be shorter, minimal and instantaneous. Keyword: Zoom Meeting, Long-distance learning, Dromology, College Students